A Few Bad Apples? Criminal Charges, Political Careers, and Policy Outcomes - Diogo Britto; Gianmarco Daniele; Marco Le Moglie; Paolo Pinotti; Breno Sampaio (Institute of Labor Economics (IZA), 2024)
We study the prevalence and effects of individuals with past criminal charges among candidates and elected politicians in Brazil. Individuals with past criminal charges are twice as likely to both run for office and be elected compared to other individuals. This pattern persists across political parties and government levels, even when controlling for a broad set of observable characteristics. Randomized anti-corruption audits reduce the share of mayors with criminal records, but only when conducted in election years. Using a regression discontinuity design focusing on close elections, we demonstrate that the election of mayors with criminal backgrounds leads to higher rates of underweight births and infant mortality. Additionally, there is an increase in political patronage, particularly in the health sector, which is consistent with the negative impacts on local public health outcomes.
Keywords: K42; J45; P16; 330; politicians; crime; audits; policies; patronage